Description of Clean and Healthy Living Behavior (PHBS) Students/I D3 Nursing Study Program STIKES Santa Elisabeth Medan During Pandemic Covid-19 in 2022 - Nasipta Ginting; Indra Hizkia Peranginan; Elisa Br Simanjuntak (Indonesian Journal of Global Health Research, 2022)
Coronaviruses are part of a large family of viruses that cause disease in animals or humans. Humans infected with the virus will show signs of respiratory tract infections ranging from flu to more serious ones. Prevention of COVID-19 transmission can be done starting from washing hands, using masks, social distancing, physical distancing, applying cough and sneezing etiquette, implementing a clean and healthy lifestyle, changing clothes, managing comorbidities, managing mental & psychosocial health and adapting new habits. carry out health protocols. The purpose of the study is to describe the behavior of students towards clean and healthy living behavior (PHBS) in the STIKes Santa Elisabeth Medan. This study uses a descriptive design with a sampling technique using a sampling of 95 respondents, how to collect data using a questionnaire and the data is analyzed in several stages, namely editing, coding, scoring, tabulating. The results show that the description of student behavior towards PHBS in STIKes Santa Elisabeth Medan is found to be "good" 33 people (34.7%), "enough" 62 people (65.3%). It is hoped that students can further increase awareness in implementing clean and healthy living behaviors (PHBS) recommended by the health department in their daily lives.